Factors Associated with the Diarrhea Incident in Children Ages 12-59 Months - Sumarah Sumarah; Salsabilla Jannah; Yuliantisari Retnaningsih; Sri Winarni (JURNAL INFO KESEHATAN, 2025)
Diarrhea remains one of the leading causes of mortality among children under five years of age and ranks as the second most common cause of death among Indonesian children aged 12–59 months. Given its endemic nature and potential to cause outbreaks, identifying modifiable risk factors is essential for effective prevention. This study aimed to analyze factors associated with the occurrence of diarrhea among children aged 12–59 months in Bantul, Indonesia. An observational analytic study with a retrospective case–control design was conducted using purposive sampling. A total of 160 children aged 12–59 months were included, comprising 80 diarrhea cases and 80 controls. Data were collected from mothers using structured questionnaires, while children’s nutritional status was assessed using the Growth Monitoring Card. Data analysis was performed using chi-square tests and multivariable logistic regression. The results demonstrated significant associations between diarrhea incidence and nutritional status (p = 0.041; OR = 2.343), economic status (p = 0.024; OR = 2.200), household water source (p = 0.016; OR = 1.209), hand-washing behavior (p < 0.001; OR = 3.646), and history of exclusive breastfeeding (p < 0.001; OR = 5.479). Multivariate analysis identified a history of exclusive breastfeeding as the strongest factor associated with diarrhea occurrence (p < 0.001; OR = 4.140; 95% CI: 1.938–8.843). In conclusion, diarrhea among children aged 12–59 months is significantly associated with nutritional status, socioeconomic conditions, water sources, hand hygiene practices, and exclusive breastfeeding history, with exclusive breastfeeding showing the greatest protective effect. Strengthening parental education and public health programs that promote exclusive breastfeeding is essential for reducing diarrhea incidence in young children.